The bilateral field advantage effect in memory precision. Issue 3 (March 2018) - Zhang, Yin; Ye, Chaoxiong; Roberson, Debi; Zhao, Guang; Xue, Chengbo; Liu, Qiang
Previous research has demonstrated that visual working memory performance is better when visual items are allocated in both left and right visual fields than within only one hemifield. This phenomenon is called the bilateral field advantage (BFA). The BFA is thought to be driven by an enhanced probability of storage, rather than by greater precision. In the present experiments, we sought to test whether the BFA can also extend to precision when the parameters of the task are modified. Using a moderate number of to-be-remembered items and 400 ms presentation time, we found better precision in the bilateral condition than in the unilateral condition. The classic BFA was still found in the form of an enhanced probability of storage, when presentation time was 200 ms. Thus, the BFA appears to convey both enhanced precision and greater probability of storage. The BFA is most likely due to the allocation of more attentional resources, when items are presented in both left and right visual fields.